Pengaruh Subtitusi Gula Palem Terhadap Sifat Organoleptik Egg Roll Tepung Kacang Koro Benguk - Windy Pujiwanti; Niken Purwidiani; Lucia Tri Pangesthi; Sri Handajani (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine: 1) the influence of palm sugar substitution on the organoleptic properties of velvet bean flour egg rolls, including aspects of color, aroma, taste, and crispiness,; and 2) the nutritional content of velvet bean flour egg rolls with the optimal palm sugar substitution, encompassing carbohydrates, proteins, fats, fibers, and minerals (calcium, phosphorus, iron). This study adopts a single-factor factorial experimental design with the independent variable being palm sugar at percentages of 50%, 75%, and 100%. The dependent variables encompass the organoleptic properties of velvet bean flour egg rolls, including color, aroma, taste, and crispiness. Data collection employs a questionnaire administered by 10 trained panelists and 20 semi-trained panelists.. The collected data is analyzed using one-way ANOVA, followed by Duncan's test for post hoc analysis. Chemical analysis of the egg rolls is conducted at the Balai Penelitian dan Konsultasi Industri Surabaya (BPKI) to determine nutritional content, including protein, carbohydrates, fats, fiber, and minerals (calcium, phosphorus, and iron). The results showed: 1) palm sugar substitution significantly influences the organoleptic properties of velvet bean flour egg rolls, including color, aroma, taste, and crispines; and 2) the chemical analysis results for the nutritional content of the best egg roll, namely the velvet bean flour egg roll with 50% palm sugar substitution, include protein 12,56%, carbohydrates 80,94%, fats 6,20%, fiber 2,18%, calcium 162,10 mg/100 g, phosphorus 30,80 mg/100 g, and iron 2,61 mg/100 g.